Rhythms during the polar night: evidence of clock-gene oscillations in the Arctic scallop Chlamys islandica. Issue 1933 (26th August 2020) - Perrigault, Mickael; Andrade, Hector; Bellec, Laure; Ballantine, Carl; Camus, Lionel; Tran, Damien
Abstract : Arctic regions are highly impacted by climate change and are characterized by drastic seasonal changes in light intensity and duration with extended periods of permanent light or darkness. Organisms use cyclic variations in light to synchronize daily and seasonal biological rhythms to anticipate cyclic variations in the environment, to control phenology and to maintain fitness. In this study, we investigated the diel biological rhythms of the Arctic scallop, Chlamys islandica, during the autumnal equinox and polar night. Putative circadian clock genes and putative light perception genes were identified in the Arctic scallop. Clock gene expression oscillated in the three tissues studied (gills, muscle, mantle edge). The oscillation of some genes in some tissues shifted from daily to tidal periodicity between the equinox and polar night periods and was associated with valve behaviour. These results are the first evidence of the persistence of clock gene expression oscillations during the polar night and might suggest that functional clockwork could entrain rhythmic behaviours in polar environments.